The Integration of the Islamic and Customary Law in Tolaki Society, Southeast Sulawesi: Islamic History and Education Perspectives - Pairin, Pairin; Syahrul, Syahrul; Badarwan, Badarwan; Samrin, Samrin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This article seeks to elucidate the assimilation of the Islamic and customary law within the Tolaki community in Konawe, Southeast Sulawesi. The Islamization of Tolaki society follows a dialogic-integrative model, similar to other Eastern Indonesian societies like Gowa-Tallo, Bone, Ternate, and Buton. This is a qualitative research and applies the philosophy of history and Islamic education for data analysis. The methods of data collection include interviews, documentations, and observations. According to this study, the majority of Tolaki people prefer Islam as their religion. The integration of the Islamic law and custom in Tolaki society is highly robust, evident through the kalo sara procedure serving as a symbol of the amalgamation of Islam and culture. The Tolaki community practices the Islamic law, which is seen in the customary fines imposed on individuals who commit customary infractions. The model of Islamization of the Tolaki community can be described as dialogical-integral. This means that the process of Islamization starts with the Sultanate and then extends to the wider community. From an Islamic educational standpoint, the process of Islamization starts with the Sultanate and progresses to the establishment of various Islamic educational institutions, including Religious Teacher Education. Subsequently, several Islamic boarding schools emerge, transforming societal perceptions towards Islamic educational institutions. Presently, there is a growing trend of the Tolaki people migrating to the mainland as a result of the favorable climate in Islamic institutions. Furthermore, the graduates of these schools are making tangible contributions to society.